Preschoolers’ Cognitive Profiles on Environmental Cleanliness: A Piagetian-Based Thematic Assessment of 6-Year-Olds - Nina Afria Damayanti; Lindawati Elisabeth Nababan; Fakhira Azzahra Syarefi; Lisda Sinaga (International Journal of Educational Practice and Policy, 2025)
Environmental cleanliness is a socially relevant yet underexplored theme in early childhood cognitive development. While preschool education often introduces hygiene routines, little is known about how young children cognitively construct meaning around cleanliness. Most studies have focused on abstract academic domains like literacy and numeracy, while real-world issues remain marginal despite their potential to stimulate rich cognitive processes. This study investigates the cognitive profiles of six-year-old children on the theme of environmental cleanliness, grounded in Piaget’s theory of the preoperational stage. It explores how children demonstrate development across four domains including symbolic thinking, memory, language use, and imagination. A thematic assessment instrument was developed and validated through expert review, comprising 13 observable indicators. Data were collected through structured observation and guided interviews with seven children in three kindergartens in Medan, Indonesia. Findings revealed that most participants were categorized as established in memory and language use, indicating strong recall and verbal explanation of cleanliness routines. However, symbolic thinking and imagination remained in the developing range, particularly in tasks involving abstraction or causal reasoning. These results highlight the importance of contextualized, thematic assessment in revealing nuanced developmental patterns and underscore the need to foster symbolic and imaginative reasoning as part of early environmental education.